Meteor from the cockpit Britain's first jet fighter - Caygill, Peter (Pen & Sword Aviation, 2010)
The Meteor is remembered as the first British jet fighter to enter squadron service and the only jet powered Allied fighter to see action in WW II. The Meteor was immensely strong and many pilots owe their lives to its rugged construction. This book looks into the aircraft's design history, development through many different variants and includes many firsthand accounts of flying the aircraft in peace and war.